2007
DOI: 10.1371/journal.pbio.0050201
|View full text |Cite
|
Sign up to set email alerts
|

Aging Hematopoietic Stem Cells Decline in Function and Exhibit Epigenetic Dysregulation

Abstract: Age-related defects in stem cells can limit proper tissue maintenance and hence contribute to a shortened lifespan. Using highly purified hematopoietic stem cells from mice aged 2 to 21 mo, we demonstrate a deficit in function yet an increase in stem cell number with advancing age. Expression analysis of more than 14,000 genes identified 1,500 that were age-induced and 1,600 that were age-repressed. Genes associated with the stress response, inflammation, and protein aggregation dominated the up-regulated expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
694
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 721 publications
(756 citation statements)
references
References 52 publications
48
694
1
4
Order By: Relevance
“…16,132 Despite these findings (or perhaps due to this dysfunction) older mice have an increased number of HSCs, although these cells demonstrate reduced repopulating potential and a propensity towards myeloid skewing. 108,[133][134][135] Together, these findings strongly support the conclusion that aging expands one or more pools of dysfunctional HPCs/HSCs that limit the hematopoietic system response, especially in times of stress. Since DNA repair processes are disrupted with aging, DNA damage accumulates in the cells of older adults.…”
Section: Effects Of Aging On Hematopoietic Expressionsupporting
confidence: 65%
See 1 more Smart Citation
“…16,132 Despite these findings (or perhaps due to this dysfunction) older mice have an increased number of HSCs, although these cells demonstrate reduced repopulating potential and a propensity towards myeloid skewing. 108,[133][134][135] Together, these findings strongly support the conclusion that aging expands one or more pools of dysfunctional HPCs/HSCs that limit the hematopoietic system response, especially in times of stress. Since DNA repair processes are disrupted with aging, DNA damage accumulates in the cells of older adults.…”
Section: Effects Of Aging On Hematopoietic Expressionsupporting
confidence: 65%
“…These investigators found an age-dependent down-regulation of genes involved in chromatin remodeling and maintenance of genomic integrity, while there was a concomitant increase in the expression of genes associated with stress responses, inflammation, and protein aggregation. 135 Rossi et al examined a slightly less differentiated population of murine LTR-HSCs, and this study found marked ARECs for genes associated with myeloid development, which may provide some insight into the age-associated myeloid skewing. 167 Furthermore, older LTR-HSCs also displayed increased expression of some genes that have previously been recognized as being involved in leukemic transformation.…”
Section: Effects Of Aging On Hematopoietic Expressionmentioning
confidence: 68%
“…Hematopoiesis in the aged shows preferential differentiation into myeloid cells at the loss of support for the B‐cell lineage. An apolar distribution of the small RhoGTPase Cdc42 and the cytoskeletal protein tubulin within the cytosol, and of histone 4 acetylated on lysine 16 (AcH4K16) in the nucleus (Florian et al , 2012) caused by increased activity of the small RhoGTPase Cdc42, as well as additional changes in epigenetic modifications referred to as epigenetic drift and altered gene expression profiles (e.g., high expression of myeloid genes) are additional hallmarks of aged HSCs (Chambers et al , 2007; Florian & Geiger, 2010; Florian et al , 2012; Beerman et al , 2013). Historically, aging of HSCs was thought to be solely influenced by stem cell intrinsic mechanisms (Rossi et al , 2005; Florian et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, quantification of HSCs by fluorescence-activated cell sorting (FACS) using cell surface markers indicate that the frequency of cells expressing stem and progenitor markers (KLS; c-Kit þ , Lin À , Sca1 þ ) increases with age in C57BL/6 mice (Sudo et al, 2000;Kim et al, 2003;Rossi et al, 2005;Pearce et al, 2007). The observed increase in HSCs with age is due to specific expansion of the HSC compartment capable of long-term reconstitution of the hematopoietic system in a recipient mouse, termed LT-HSCs (Rossi et al, 2005;Chambers et al, 2007;Pearce et al, 2007). Notably, the majority of LT-HSCs are relatively quiescent and do not undergo major changes in cell cycle status with age, suggesting that HSC expansion is not caused by substantial changes in HSC cycling (Cheshier et al, 1999;Sudo et al, 2000;Chambers et al, 2007;Rossi et al, 2007b).…”
Section: Defects In Number In Aging Stem Cellsmentioning
confidence: 99%
“…The observed increase in HSCs with age is due to specific expansion of the HSC compartment capable of long-term reconstitution of the hematopoietic system in a recipient mouse, termed LT-HSCs (Rossi et al, 2005;Chambers et al, 2007;Pearce et al, 2007). Notably, the majority of LT-HSCs are relatively quiescent and do not undergo major changes in cell cycle status with age, suggesting that HSC expansion is not caused by substantial changes in HSC cycling (Cheshier et al, 1999;Sudo et al, 2000;Chambers et al, 2007;Rossi et al, 2007b). Although FACS-based analysis and in vitro assays might characterize different populations of stem cells-perhaps more committed progenitors in the case of in vitro assays-these data raise the possibility that the genetic background of mouse strains influences the proliferative control of HSCs and their progeny during aging (de Haan et al, 1997;de Haan and Van Zant, 1999).…”
Section: Defects In Number In Aging Stem Cellsmentioning
confidence: 99%